Research on the Internal and External Monitoring Mechanism of the Electricity Market in the Spot Market: From the Perspective of the Evolutionary Game Theory - Jin, Luosong; Liu, Weidong; Chen, Cheng; Ji, Jingping; Wang, Wei (Frontiers in Energy Research, 2022)
The internal and external monitoring mechanism is a beneficial monitoring mode which is in line with the current national condition, the situation of power grid and the construction progress of power spot market. However, the independence of third-party monitoring agencies cannot be completely guaranteed because of the incomplete management system of China's electricity market at present. Therefore, the market is prone to power rent-seeking in which third-party monitoring agencies conspire with the market internal monitoring organization. Based on the evolutionary game theory, this paper builds a coordination game model between third-party monitoring agencies and the market internal monitoring organization, as well as an asymmetric coordination game model between the interest group composed of internal and external monitoring agencies and government regulatory authorities. By analyzing the evolutionarily stable strategy of each game participant, the paper identifies the underlying factors that affect the strategic choices made by internal and external monitoring agencies and government regulatory authorities, and then put forward some reasonable suggestions for reducing the probability of third-party monitoring agencies colluding with internal monitoring organization, so that the efficiency of internal and external monitoring mechanism can be improved.